A Two-Phase Induction Generator System using the Vector Control Technique - Rujidam, Navee; Jamshidpour, Ehsan; Kinnares, Vijit; Baghli, Lotfi; Takorabet, Noureddine (My University, 2024)
This paper proposes a vector control drive system for a two-phase induction generator. The system comprises a single-phase full-bridge grid converter and a two-phase three-leg voltage source inverter, both controlled using vector control. The grid converter utilizes voltage-oriented control, the inverter is managed through field-oriented control. This approach enhances the electromagnetic torque performance of the two-phase induction generator. The system is simulated using MATLAB/Simulink, and the simulation results indicate that the generator torque exhibits a smooth and fast transient response. Additionally, the grid current of the system closely approximates a sinusoidal waveform with a near unity power factor.
Keywords: field-oriented control; two-phase induction generator; voltage-oriented control